The avifauna of the Barito Ulu region. Central Kalimantan - Roger Wilkinson; Guy Dutson; Ben Sheldon; . Darjono; Yus Rusila Noor (Indonesian Ornithologists’ Union, 1991)
As part of the more general studies of the Barito Ulu Project, a detailed study was made of the avifauna in July-September 1989. The survey area, which lies at the geographical centre of the island of Borneo, consists mainly of primary forest in hilly terrain, and this Is the first detailed study that has been made In the hills of Kalimantan for many decades. A week was also spent in montane forest at 800-1000 m. An appendix lists 226 species that were recorded. The avifauna includes 15 Bornean endemics, and extensions to known range are made for Spizaetus alboniger, Arborophila hyperythra and Megalaima eximia. Data are provided also on 20 species for which there are no recent Kalimantan records. While species described as 'slope specialists' predominated, the presence of some 26 'extreme lowland specialists' may have significance for conservation, for example Lophura erythrophthalma, Melanoperdix nigra. Pitta baudi, Malacopteron albogulare and Pityriasis gymnocephala.